Valmet Chiral Schiff‐Base Ligands And Their Copper(II) Complexes as Organo, Homogeneous and Heterogeneous Catalysts for Henry, Cyanosilylation and Aldol Coupling Reactions. Issue 21 (6th September 2021) - Arora, Zinnia; Eftemie, Diana‐Ioana; Spinciu, Adela; Maxim, Cătălin; Hanganu, Ana‐Maria; Tudorache, Madalina; Cojocaru, Bogdan; Pavel, Octavian D.; Granger, Pascal; Andruh, Marius; Pârvulescu, Vasile I.
Abstract: Cyanosilylation, aldol coupling and asymmetric Henry reactions were carried out with L ‐ and D ‐valmet ligands in different configurations: i) coordinated to sodium ions, as organocatalysts, with week base properties, ii) complexes with copper(II), as homogeneous catalysts, and iii) immobilized copper(II) complexes onto graphene oxide (GO) as heterogeneous catalysts. For the reaction of benzaldehyde and nitromethane in water these afforded an asymmetric Henry reaction, with a spectacular increase of the conversion and ee (92.5 and 95.8 %, respectively) after the deposition on GO. Ligand complexed copper was also effective for cyanosilylation and Aldol coupling reaction. Abstract : Immobilization: L ‐ and D ‐valmet ligands prepared from the condensation of o ‐vanillin and L ‐, respectively, D ‐methionine exhibit a different catalytic behavior affording asymmetric Henry condensation, cyanosilylation reaction after complexation with copper or the Aldol reaction after the immobilization of these complexes onto GO.